RETRACTED ARTICLE: Knockdown of hsa_circ_0058124 inhibits the proliferation of human lung cancer cells by up-regulation of miR-1297 - Xiaoliang Li; Qianqian Zhang; Zhigang Yang (Artificial Cells, Nanomedicine, and Biotechnology)
We, the authors, Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Xiaoliang Li, Qianqian Zhang & Zhigang Yang. (2020). Knockdown of hsa_circ_0058124 inhibits the proliferation of human lung cancer cells by up-regulation of miR-1297. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 584–593, DOI: 10.1080/21691401.2020.1725537Since publication, the authors noticed that the transfection reagent used in the reported experiments was contaminated. As this directly impacts the validity of the reported results and conclusions the authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure the integrity of the scholarly record.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.